Miniaturized frequency selective surface for gain and bandwidth enhancement in millimeter-wave antennas - Zabri @ Suhaimi, Siti Normi; Shairi, Noor Azwan; Mohamad Ryeeshyam, Mohamad Fattullah; Mohamad, Sarah Yasmin (Human Resource Management Academic Research Society, 2024)
This paper studies the characteristics of a Microstrip Patch Antenna (MPA) at the resonant frequency of 77 GHz for millimeter-wave applications, enhanced using a miniaturized Frequency Selective Surface (FSS). The proposed FSS unit cell is derived from a modified Swastika structure and serves as the fundamental element of a 2x2 periodic array. Acting as a reflective plane, the FSS is mounted onto the microstrip patch antenna to improve performance metrics such as return loss, bandwidth, gain, and directivity. The antenna is designed and analyzed in CST software using a Rogers 3003 substrate with a dielectric constant of 3.0 and a thickness of 0.254 mm. The gain is improved from 6.730 dB to 7.519 dB, with the resonant frequency operating at 77.42 GHz. The FSS also enhances the return loss bandwidth and directivity, making this antenna suitable for automotive radar applications.